An adaptive approach to mitigate the effects of I/Q imbalance and multipath channel - Haq, K.; Chung, Kah-Seng (IEEE Computer Society, 2013)
It is well known that dual-branch receivers suffer from in-phase (I) and quadrature (Q) imbalance problems resulting in distortion and poor signal quality. This paper presents a novel technique, incorporating adaptive estimation and compensation, to mitigate the combined effects of I/Q imbalance and multipath channel on the received signal. Estimation of the channel and I/Q imbalance parameters is performed in time domain using a training sequence. Based on the estimated I/Q imbalance and channel parameters, signal compensation are performed in the frequency domain. Computer simulations have shown that the proposed scheme is effective in mitigating the combined effects of I/Q imbalance and multipath fading for QPSK and 16-QAM modulation. The Symbol Error Rate (SER) achieved for the compensated 16-QAM signal is 10-4, at an SNR of 20dB, which is the same for ideal 16-QAM signal, at an SNR of 19dB.